Avaliação clínica, laboratorial e radiográfica de pacientes com espondiloartropatias, no estado do Pará: Período de janeiro de 2006 a dezembro de 2007 - KAHWAGE, Carolina Barros (2023)
BACKGROUND: Spondyloarthropathies is a group of deseases that show inflamatory axial pain associated to assimetric peripheral arthritis, sacroiliitis,enthesopathy, family history,and HLA-B27 association, extra articular involvement and lack of reumatoid factor. They include ankylosing spondylitis; psoriatic arthritis; reactive arthritis; Reiter´s syndrom; undifferentiated spondyloarthropaty; juvenile spondyloarthropaty.The prevalence of spondyloarthropathies varies around the world. In the last years, the concept of spondyloarthropathies has become wider and the diagnostic of the different diseases into the group has been increasingly known. OBJECTIVE: To describe the epidemiological, clinical and radiological profile of a series of patientes from Pará. METHODS: During the period 2006-2007, it was analised the data from a standardized protocol of investigation to study epidemiological, clinical,and radiological variables of 41 spondyloarthropatical patients. RESULTS: The series was constituded predominantly by psoriatic arthritis (41,5%), ankylosing spondylitis(24,4%), reactive arthritis (19,5%), undifferentiated spondyloarthropaty (12,2%) and juvenile spondyloarthropaty (2,4%). There was a predominance of male patients (68,3%). Regarding race 70,7% were white, 22% mulattos, and 7,3% black.Mean age was 50,1 years. HLA-B27 was positive in 41,4% of the tested patients, and familial history of a defined spondiloarthropaty was referred by22%. The most commom extra articular involvement was psoriasis with 39%, followed by dactilitis 36,6% and nail changes 29,3%. Peripheral arthritis was the most commom extra axial characteristic, found in 95% of the tested patients. The clinical sacroiliitis had a 65,8% prevalence while the radiological sacroiliitis was 87,8%. Regarding treatment, AINES were used by 100% of the patients, metotrexato 78%, corticosteroids 70,7%, infliximab 24,4%, leflunomide 22% and sulfasalazine 19,5%. Mean BASDAI was 4,4 and BASFI was 3,8. CONCLUSION: The psoriatic arthritis was the EAP most comumm, which explains the high mean age, comparing with literature; and a lower rate regarding masculine and feminine sex; and peripheral arthritis prevalence. In EA the BASFI found was twice the mean value among the others EAP, which shows that this desease can highly compromise the life quality.